A reestruturação do Serviço Social no Instituto Nacional do Seguro Social em Sergipe no período de 1998 a 2003 - Rodrigues, Rita Regina Domingos da Cruz (2017)
The study proposed to analyze the Social Service in Social Security in Sergipe, from 1998 to 2003, when a redesign in the organizational structure occurs due to measures foreseen in the social security reform, which include, among them, the extinction of Social Service of the institutional framework. The intention was to analyze social security policy, initially presenting aspects about the capitalist system, social rights, social policy and how the implantation of neoliberal politics in Brazil, even if late, when compared to the central capitalist countries, directly interfere in Brazilian social security, affecting the rights of the workers and of his family, including the servants of the institution itself, in the case of the Social Workers. The research is inspired by dialectical historical materialism, based on a critical theoretical analysis on Brazilian social security policy, making brief contextualizations about its origin and evolution until inserted as a policy integral to the Brazilian Social Security and undergo deep reforms that changed the conception protection. The intention was also to reflect on the trajectory of the Social Welfare Service and the refutations of the counterreform of the Brazilian State through the social security reforms that occurred in the 1990s and 2000s. These had as a consequence the flexibilization and the precariousness of working conditions, allied to reduction of the State's role in relation to social policies, undermining labor and social security rights, as well as modifying the institutional structure. In Sergipe, the social security reform caused the drastic loss of team members of Social Service, greatly affecting the professional doing as well as the visibility of this professional that had its importance questioned and seriously threatened after institutional restructuring resulting from this counterreformation. It was intended to adopt a critical stance that sought to break with the superficial analysis and to overcome the immediacy of the real. This is an exploratory, qualitative approach. For data collection, primary and secondary documentary sources, official documents and documents were used as well as a semi-structured interview with Social Service professionals belonging to the National Social Security Institute in Sergipe, respecting the ethical aspects of this type of research.